Bacterial cell immobilization beads having excellent transformation activity and method for producing the same

JP7641281B2Active Publication Date: 2025-03-06SAMYANG CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022525216
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-30
Filing Date
2020-10-30
Publication Date
2025-03-06
Estimated Expiration
2040-10-30

AI Technical Summary

Benefits of technology

【0061】 本発明の一例による乾燥ビーズ、復原ビーズ、およびこれらを利用したアルロース生産は、体積および重量が乾燥前ビーズに比べて減少して保管および流通が容易であり、単位体積当たりカラム充填量を増加させてアルロース生産量を増加させ、保管安定性が高くて従来の保管過程で微生物の汚染によるビーズの結合力弱化および分解によりビーズ外部に菌体流出および転換活性減少になる問題点を解消し、そこで、長期間にわたって安定的に高いアルロース生産量を提供することができるという長所がある。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641281000013
    Figure 0007641281000013
  • Figure 0007641281000014
    Figure 0007641281000014
  • Figure 0007641281000015
    Figure 0007641281000015
Patent Text Reader

Abstract

The present invention relates to bacterial cell-immobilized beads and a method for producing the same. More specifically, the present invention relates to bacterial cell-immobilized beads that exhibit excellent transformation activity of the bacterial cells contained in the immobilized beads and maintain the transformation activity even during distribution and storage, a method for producing the bacterial cell-immobilized beads, and uses utilizing the transformation activity of the beads.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to bacterial cell-immobilized beads and a method for producing the same, more specifically to bacterial cell-immobilized beads which have excellent transformation activity of the bacterial cells contained in the immobilized beads and which maintain the transformation activity even during distribution and storage, a method for producing the bacterial cell-immobilized beads, and uses utilizing the transformation activity of the beads. [Background technology]

[0002] Allulose is gaining attention as a dietary sweetener, but since it is a rare sugar, a monosaccharide that is found extremely rarely in nature, it is necessary to develop a technology to efficiently produce allulose in order to apply it to the food industry. Conventional methods for producing allulose are mainly known to be a method of producing it through a chemical synthesis process and a biological production method using microbial enzymes. Recently, environmentally friendly biological production methods have been preferred over chemical production methods for food ingredients, and for this reason, many studies have been conducted on using microorganisms in allulose production methods.

[0003] Allulose epimerization enzyme, which is a fructose-converting allulose-producing enzyme possessed by microorganisms that produce allulose, is eluted outside the cells, and production methods using enzyme immobilization methods and production methods using cell-containing carrier immobilization methods are industrially used. Among these, the production method using a cell immobilization carrier without a process of extracting the enzyme from the cells is a more economical method and is mainly applied industrially. Alginic acid, which is suitable for manufacturing food materials, is used as a cell immobilization carrier used in allulose production. Alginic acid is a food additive and is used in various fields such as lactobacillus capsules, beverages, medical tissue engineering materials, and drug delivery vehicles. Alginic acid is widely used as a carrier (beads) because it easily forms hydrogel, and is particularly widely used for immobilizing enzymes and cells. In addition, beads using alginic acid or its salts are porous materials with swelling and elasticity, and are advantageous because they can stably immobilize cells and enzymes by randomly forming beta-1,4 bonds.

[0004] However, the beads immobilized with alginic acid will spoil if exposed to a high moisture content environment where microorganisms can grow for several hours, and as a result, the binding strength of the beads will weaken, and the activity of the allulose epimerization enzyme in the bacteria will decrease rapidly as the bacteria are released from the carrier, thereby slowing down the allulose production rate during the fructose conversion allulose production reaction.

[0005] In addition, although the porous characteristics are well preserved when beads made of alginic acid or its salts are immersed in an aqueous solution, there is a problem that storage and distribution in anything other than an aqueous solution is difficult without special chemicals and measures against contamination. In other words, since the moisture-containing bacteria-immobilized alginic acid carrier exists in an immersed state just as when it is produced, it is difficult to store it during mass production, and there may be complicated restrictions such as high costs and the need to store it in a liquid state during distribution.

[0006] In addition, the optimum pH for the activity of most enzymes and cells is around pH 7. At around pH 7, the binding strength of alginate beads weakens, causing swelling and decomposition. Also, the binding strength weakens further at high temperatures, limiting its industrial application.

[0007] In order to solve these problems, a method is needed to produce dry beads with excellent storage and distribution properties that maintain conversion activity by establishing a manufacturing process and conditions for removing moisture contained in alginate carriers on which biocatalysts such as bacteria and enzymes are immobilized. Summary of the Invention [Problem to be solved by the invention]

[0008] One example of the present invention provides dry beads for producing allulose, in which cells of a strain of the genus Microbacterium having allulose conversion activity that produces allulose from fructose are immobilized in alginic acid or a salt thereof, and a method for producing the same.

[0009] One example of the present invention provides reconstituted beads obtained by reconstituting the dried beads for producing allulose from fructose with water or a fructose liquid, and a composition for producing allulose using the same, or a method for producing an allulose-containing product from a fructose-containing substrate using the same.

[0010] The present invention also provides a composition for producing allulose, which comprises the dried bacterial cell-immobilized beads, or a method for producing an allulose-containing product from a fructose-containing substrate using the composition. [Means for solving the problem]

[0011] One example of the present invention relates to dried beads having a low moisture content, in which bacterial cells of a strain of the genus Microbacterium having allulose conversion activity that produces allulose from fructose are immobilized on a carrier and dried, and a method for producing the same; restored beads obtained by restoring the dried beads and a method for producing the same; a composition for producing allulose containing the dried beads and / or the restored beads; and a method for producing allulose.

[0012] The dry beads containing the bacteria immobilized on the carrier according to the present invention have a low moisture content and excellent storage stability and thermal stability.

[0013] In addition, the restored beads obtained by restoring the dried beads have an excellent property recovery rate and show a similar level of properties to the beads before drying, and have a relatively equal or similar level of allulose conversion reaction activity. The dried beads have an increased allulose production amount by reducing the volume of the beads and increasing the column loading amount per unit volume, and have the advantage of being able to provide a stable and high allulose production amount for a long period of time by producing beads with high storage stability, which is a problem recognized in the conventional technology that non-dried beads in a water-containing state have a weakened binding force and decomposition of the beads due to microbial contamination during storage, resulting in the leakage of bacteria outside the beads and a decrease in conversion activity.

[0014] One example of the present invention relates to dry beads comprising alginic acid or an alginate as a carrier and cells of a strain of the genus Microbacterium that produces an allulose epimerization enzyme immobilized on the carrier, the beads having a moisture content of 14% or less.

[0015] Yet another embodiment of the present invention relates to reconstituted beads obtained by reconstituting the above-mentioned dried beads with water or fructose solution.

[0016] The moisture content or water content of the dried beads according to the present invention may be 14% or less, and the dried beads may have a volume or weight of 50% or less after drying, based on 100% volume or weight of undried beads having a moisture content of 90% or more.

[0017] One example of the present invention relates to dry beads having a low moisture content, in which cells of a strain of the genus Microbacterium having allulose conversion activity that produces allulose from fructose are immobilized on a carrier and dried.

[0018] Specifically, the dry beads according to the present invention may have at least one of the following properties: (i) A moisture content of 14% or less; (ii) The weight after drying is 35% or less based on 100% weight of the wet beads; (iii) Bulk density is 0.6 to 0.8 kg / L; (iv) the allulose conversion activity of the dried beads after storage for 38 weeks at 25°C is 60% or more, based on the allulose conversion activity of the dried beads immediately after production (100%); (v) the allulose conversion activity of the dried beads after storage for 38 weeks at 60°C is 50% or more, based on 100% conversion activity of the dried beads immediately after production; (vi) having a reaction column packing rate (volume %) of 35% or less based on a reaction column packing rate (volume %) of wet beads of 100%, and (viii) The average particle size of the restored beads obtained by restoring the dried beads is 1.1 to 1.9 mm.

[0019] Another embodiment of the present invention relates to reconstituted beads obtained by reconstituting the dried beads with water or fructose solution. Specifically, the reconstituted beads may have at least one of the following characteristics: (i) A moisture content of 90% or more; (ii) The reaction column packing rate (volume %) is 35% or more, based on 100% of the reaction column packing rate (volume %) of wet beads; (iii) the average particle size of the beads is 1.1 to 1.9 mm; (iv) The average particle size of the restored beads is 120-190% of the average particle size of the dry beads, (v) the substrate flow rate (mL / min) at which a 50% by weight fructose solution is passed through and the allulose conversion rate is maintained at 25% or more is 110 to 300 based on 100% undried beads; and (vi) The allulose content of the allulose conversion reaction product obtained from the fructose-containing raw material is about 110% or more based on 100% allulose production amount relative to the beads before drying.

[0020] In detail, the moisture content or water content of a dry bead according to one embodiment of the present invention may be 14% or less, 12% or less, 10% or less, 9.9% or less, 9.5% or less, 9.0% or less, 8.9% or less, 8.7% or less, 8.5% or less, or 8% or less, and the lower limit of the moisture content may be 1% or more, 2% or more, 3% or more, 4% or more, or 5% or more, and the range of the moisture content may be a combination of the upper and lower limits, for example, 1 to 14%, 2 to 12%, 3 to 10%, 3 to 8%, 4 to 8%, or 5 to 8%.

[0021] The dried beads may have a weight of 35% by weight or less, 30% by weight or less, 25% by weight or less, 20% by weight or less, 17% by weight or less, 15% by weight or less, 12% by weight or less, 10% by weight or less, or 8% by weight or less, preferably 30% by weight or less, 25% by weight or less, 20% by weight or less, 17% by weight or less, 15% by weight or less, 12% by weight or less, 10% by weight or less, or 8% by weight or less, based on 100% weight of the wet beads, for example, wet beads having a moisture content of 90% or more. Specifically, the weight of 100 g of the wet beads recovered from the solution after drying may be 50 g or less, for example, 10 g or less after drying. The weight (weight) change of the dried beads is expressed as a relative percentage value by measuring the weight before drying and the weight after drying, and the weight before and after drying have the same measurement unit.

[0022] The dried beads according to the present invention have an excellent recovery rate of physical properties of the beads upon restoration, and the efficiency of the allulose conversion reaction is relatively similar to the physical properties of the beads before drying.

[0023] In addition, the dry beads may be 35% or less, 30% or less, 25% or less, 20% or less, 17% or less, 15% or less, 13% or less, or 11% or less based on a reaction column filling rate (volume %) of undried beads, for example, undried beads having a moisture content of 90% or more, of 100%, for example, 1.0 to 35%, 1.0 to 30%, 1.0 to 25%, 1.0 to 20%, 1.0 to 20%, 1.0 to 17%, 1.0 to 15%, 1.0 to 13%, 1.0 to 11%, 3.0 to 35%, 3.0 to 30%, %, 3.0-25%, 3.0-20%, 3.0-20%, 3.0-17%, 3.0-15%, 3.0-13%, 3.0-11%, 5.0-35%, 5.0-30%, 50-25%, 5.0-20%, 5.0-20%, 5.0-17%, 5.0-15%, 5.0-13%, 5.0-11%, 5.5-35%, 5.5-30%, 5.5-25%, 5.5-20%, 5.5-20%, 5.5-17%, 5.5-15%, 5.5-13%, or 5.5-11%.

[0024] Specifically, the volume of the beads after drying may be 35 mL or less, for example 15 mL or less, for 100 mL of beads before drying recovered from the solution. The volume change of the dried beads is expressed as a relative percentage value by measuring the volume before drying and the volume after drying, and the volumes before and after drying have the same measurement unit.

[0025] The dried beads have a reduced volume and an increased density due to a reduction in the moisture content of the beads of the same weight. The dried beads according to the present invention have a reduced volume and weight compared to the beads before drying, making them easy to store and distribute. The dried beads produce beads with high storage stability by reducing the volume and particle size of the beads to increase the column loading per unit volume and increase allulose production, and have the advantage of being able to provide a stable and high allulose production rate for a long period of time by solving the problem that has been previously encountered with non-dried beads containing moisture, which have weakened binding strength and decomposition of the beads due to microbial contamination during storage, resulting in the leakage of bacteria outside the beads and a decrease in conversion activity.

[0026] The dry beads according to the present invention have excellent storage stability and thermal stability, and have the advantage of maximally maintaining allulose conversion activity before drying. When preparing dry beads, it is important to have properties and activity close to those of the beads before drying.

[0027] Specifically, the dry beads may have an allulose conversion activity of 60% or more, 70% or more, 75% or more, 80% or more, 85% or more, 90% or more, 91% or more, 92% or more, 93% or more, or 94% or more after storage for 38 weeks at a temperature condition of 25°C after production, based on 100% conversion activity of the dry beads immediately after production. The dry beads may have an enzyme titer of 50% or more, 60% or more, 70% or more, or 75% or more after storage for 38 weeks at a temperature condition of 60°C after production, based on 100% conversion activity of the dry beads immediately after production.

[0028] An example of the measurement of the storage stability is carried out under the condition that the dried beads are stored in a fructose-containing substrate solution. The stored beads are packed in a reaction tower, and a fructose-containing substrate of 50 brix (%) adjusted to a temperature of 50°C and a pH of 6.5 to 7.2 is passed through the reaction tower packed with the beads to carry out an allulose conversion reaction at a flow rate that maintains an allulose conversion rate of 25% or more, and the allulose contained in the obtained conversion reaction product is quantified. The allulose conversion activity is measured in the same manner as for the beads before storage, and can be expressed as a percentage of relative conversion activity based on the allulose conversion activity of the beads before storage being 100%. The fructose-containing substrate may be a fructose-containing raw material having a solid content of 40 to 60% by weight and a fructose purity of 30 to 99% (w / w).

[0029] In addition, the dry beads of the present invention can provide high conversion rates and production amounts for a longer period of time in producing allulose from fructose-containing substrates. Specifically, the dried beads have an allulose content of about 110% or more, 120% or more, 130% or more, 140% or more, 150% or more, 160% or more, 170% or more, or 180% or more, based on 100% allulose production, when the dried beads are reconstituted with fructose liquid, and the allulose content of the allulose conversion reaction product obtained from the fructose-containing raw material may be about 110% or more, 120% or more, 130% or more, 140% or more, 150% or more, 160% or more, 170% or more, or 180% or more, based on 100% allulose production, compared to the beads before drying, and preferably 150% or more, 160% or more, 170% or more, or 180% or more, for example, 101 to 300%, 105 to 300%, 110 to 300%, 120 to 300%, 130 to 300%, or 140 to 300%. Preferably, the bacterial cells used in the beads may be bacterial cells heat-treated at a temperature of 30 to 70°C, and the allulose content of the allulose conversion reaction product using restored beads restored with fructose liquid may be about 150% or more, 160% or more, 170% or more, 180% or more, 190% or more, or 200% or more based on 100% allulose production using the beads before drying, and the upper limit may be 205% or less, 210% or less, 220% or less, 230% or less, 250% or less, 260% or less, 270% or less, 280% or less, 290% or less, or 300% or less, for example, a numerical range that is a combination of the lower limit and the upper limit.

[0030] The restoration beads may have a substrate flow rate (mL / min) at which fructose liquid is passed through and the allulose conversion rate is maintained at 25% or more, which may be 0.15 or more, 0.17 or more, 0.20 or more, 0.22 or more, or 0.24 or more, for example, 0.15 to 0.5, 0.17 to 0.5, 0.20 to 0.5, 0.22 to 0.5, or 0.24 to 0.5.

[0031] According to one embodiment of the present invention, when the dried beads are reconstituted with water or fructose liquid, for example, when the dried beads are filled into a reactor used for producing allulose, they can be restored to their original spherical shape with water or fructose liquid.

[0032] Specifically, the restored beads obtained by restoring the dried beads according to the present invention may have a reaction tower filling rate (volume %) of 35% or more, 40% or more, or 45% or more, based on the reaction tower filling rate (volume %) of the undried beads being 100%.

[0033] According to one embodiment of the present invention, the dried beads need to be restored to their original shape before being used in a reaction to convert fructose to allulose. The restoration method can be performed by adding the dried beads to a reaction medium or water containing fructose to restore the beads to their original shape. Specifically, 10 g of the dried beads are placed in a beaker, and then 200 mL of water is added at room temperature, and the beads are stirred at a speed of 100 rpm for 30 minutes or more to restore the beads to a shape close to their original spherical shape.

[0034] According to one embodiment of the present invention, the dried beads before restoration are introduced into a reaction tower, and then the substrate for the conversion reaction used in the production of allulose is passed or circulated at a reaction temperature of 50°C and a supply flow rate of 0.2 to 0.5 SV to hydrate the dried beads and restore them to their original form.

[0035] The average particle size of the reconstituted beads obtained by reconstituting the dried beads may be 1.1 to 1.9 mm, 1.15 to 1.9 mm, 1.2 to 1.9 mm, 1.25 to 1.9 mm, 1.3 to 1.9 mm, 1.1 to 1.8 mm, 1.15 to 1.8 mm, 1.2 to 1.8 mm, 1.25 to 1.8 mm, 1.3 to 1.8 mm, 1.1 to 1.7 mm, 1.15 to 1.7 mm, 1.2 to 1.7 mm, 1.25 to 1.7 mm, 1.3 to 1.7 mm, 1.1 to 1.6 mm, 1.15 to 1.6 mm, 1.2 to 1.6 mm, 1.25 to 1.6 mm, or 1.3 to 1.6.

[0036] The average particle size (mm) of the restored beads obtained by restoring the dried beads may be 120% or more, or 130% or more, based on the average particle size (mm) of the dried beads as 100%, for example, 120% or more to 190%, 130% or more to 190%, 120% or more to 180%, 130% or more to 180%, 120% or more to 170%, 130% or more to 170%, 120% or more to 160%, or 130% or more to 160%.

[0037] Specifically, the volume of the reaction column may be restored to 40% or more, for example, 40 to 70%, based on the initial reaction column filling volume of 100%. In this way, the reaction column filling rate is increased compared to wet beads, and the productivity per unit volume can be higher than that of wet beads.

[0038] According to one embodiment of the present invention, there is provided a method for producing dry beads having a low moisture content, in which cells of a strain of the genus Microbacterium having allulose conversion activity that produces allulose are immobilized on a carrier and dried.

[0039] The characteristics of the dry beads are as described above in the description of the dry beads. More specifically, the method for producing the dried beads includes a bead formation step of immobilizing the bacterial cells on a carrier and a drying step, and may optionally include one or more additional steps consisting of a heat treatment step of the bacterial cells used to form the beads, a low-temperature curing step of the beads, and a bead coating step.

[0040] In the manufacturing method according to the present invention, the bead formation step can be carried out by adding dropwise a mixed solution containing allulose-producing bacteria or an enzyme and alginic acid or a salt thereof as a carrier to a reaction solution containing a divalent cation chloride compound.

[0041] In addition, after the step of forming the beads, the method may include one or more treatment steps selected from the group consisting of a step of hardening the bacteria or enzyme-containing beads, a step of washing off the divalent cation chloride compound, and a step of treating the bacteria or enzyme-containing beads with a fructose-containing substrate. After the formation of the beads, the additional steps may be performed by methods known to those skilled in the art, and are not particularly limited.

[0042] An example of the bead formation step is to add the bacterial cells of the strain and the enzyme produced by the strain to a sodium alginate solution having a volume 1 to 2 times that of the bacterial cells, a culture solution containing the enzyme produced by the strain, or a homogenate of the strain, and mix them, and then drop the resulting mixture into a calcium ion solution of about 0.2 M using a syringe pump and a vacuum pump to produce beads. The enzyme may be purified from the bacterial strain, the culture of the strain, or the homogenate of the strain by a conventional method such as dialysis, precipitation, adsorption, electrophoresis, affinity chromatography, ion exchange chromatography, etc.

[0043] In the present invention, alginic acid or its salt is used as the carrier, and the alginate is not particularly limited, and examples thereof include sodium alginate, potassium alginate, magnesium alginate, and ammonium alginate. For example, the alginic acid, sodium alginate, or potassium alginate as the carrier may have a viscosity of 2,000 to 50,000 cps. In addition, the concentration of the alginate solution in the bead formation step may be 1% by weight to 10% by weight, preferably 1% by weight to 8% by weight, and more preferably 2% by weight to 5% by weight, taking into consideration the convenience of the aggregate formation and the manufacturing process, but is not limited thereto.

[0044] The allulose-producing bacteria may be a wild-type strain that produces allulose epimerization enzyme or a recombinant strain into which a gene encoding the allulose epimerization enzyme has been introduced, or may be a strain that produces allulose epimerization enzyme or a recombinant strain into which a gene encoding the allulose epimerization enzyme has been introduced, and the bacteria or enzyme obtained from the strain may be used.

[0045] The cells immobilized on the beads may be cells obtained by heat-treating a solution containing the cells at a temperature of 30 to 70°C, or 30 to 65°C, 40 to 65°C, 50 to 63°C, for example, at 60°C, and the heat treatment time may be 0.1 to 2 hours. The allulose-producing cells may be cells recovered in a culture solution or cells obtained by heat-treating the culture solution. The heat-treated cells themselves (allulose conversion activity measured on the cells, not on the beads) may have a relative allulose conversion activity of 101% or more, 105% or more, 110% or more, for example 101 to 160%, compared to the cells before heat treatment. In addition, the viscosity of the mixed solution of the bacterial cells and alginic acid or a salt thereof in the bead formation process, when measured at 25°C using a mixed solution containing pre-heat-treated bacterial cells at a bacterial cell concentration of 2% (w / w) and alginic acid at 2% (w / w), may be 90% or less, for example, 4,000 to 6,000 cps, compared to that of a mixed solution containing non-heat-treated bacterial cells.

[0046] In one example of the heat treatment method, immobilized beads mixed with alginic acid and bacteria are dried at 20 to 70°C to reduce the moisture content of the beads to 14% or less, thereby producing dried beads with a volume or weight of about 50% or less of the initial volume or weight of the beads before drying (100%).

[0047] In one embodiment of the present invention, the strain producing the allulose epimerization enzyme may be a strain capable of producing the allulose epimerization enzyme in high yield while having high stability, and is preferably a strain of the genus Microbacterium, such as Microbacterium foliorum, Microbacterium oxydans, or Microbacterim phyllosphaerae, but is not limited thereto.

[0048] In the method for producing dry beads for producing allulose, it is preferable not to perform a freezing process, since there is a problem that the activity of the bacteria is reduced during the freezing process, and when the freeze-drying process is performed in large quantities, there is a problem that the production cost increases sharply. Specifically, the dry beads can be dried by using air or wind, and the air temperature is 20 to 70°C, for example, air having a temperature of 40 to 50°C is used to circulate the air for several hours.

[0049] Specifically, the bead formation process may involve treating the beads with divalent metal ions alone, or may involve treating the beads with divalent metal ions and then coating the beads with a swelling inhibitor.

[0050] The step of treating with a divalent metal can treat beads with one or more divalent metal ions selected from the group consisting of Mn2+, Zn2+, Co2+, Mg2+, Ni2+, Fe2+, and Cu2+. Specifically, the step can be carried out by supporting beads containing enzymes or bacteria in an aqueous solution or fructose-containing substrate solution to which the divalent metal ions have been added, or by passing the aqueous solution or fructose-containing substrate solution to which the divalent metal ions have been added through a column packed with the beads. The content of the divalent metal ions contained in the aqueous solution or fructose-containing substrate solution to which the divalent metal ions have been added can be 1 mM to 15 mM, but in order to have a sufficient compression effect on the beads, the treatment is preferably carried out at 5 mM to 10 mM.

[0051] The step of coating the beads with the swelling inhibitor can be carried out by immersing or adding the beads to a solution containing the swelling inhibitor. The swelling inhibitor may be at least one selected from the group consisting of chitosan, chitin, polyethylene glycol (PEG), polyethyleneimine (PEI), chito-oligosaccharide, and polylysine. When chitosan-oligosaccharide is used, the swelling inhibitor may have a weight average molecular weight in the range of 700 to 9,000, but is not particularly limited thereto. The concentration of the swelling inhibitor solution in the coating step may be 0.1% by weight to 10% by weight, preferably 0.1% by weight to 5% by weight, but is not limited thereto.

[0052] Further embodiments of the present invention provide a composition for producing allulose comprising dry beads containing the fungus and a carrier, or a method for producing allulose using a fructose-containing substrate by using the dry beads.

[0053] Preferably, the allulose production method of the present invention can be carried out by filling a column with beads containing enzymes or bacteria and passing a fructose-containing substrate solution through it, and a person skilled in the art to which the present invention pertains can easily select the enzymes, bacteria, or immobilization carriers that are more suitable for the enzymes, bacteria, or immobilization carriers used.

[0054] In one embodiment of the present invention, when a fructose solution is supplied at a certain concentration to a packed column packed with bacteria containing allulose epimerization enzyme, an epimerization reaction is carried out by the immobilized bacteria, and fructose is converted to allulose. The converted allulose can be used as pure allulose after separation and purification using a separation column.

[0055] As used herein, an immobilized reactor refers to a reactor in which the reaction for producing allulose occurs by a bacterial cell or enzyme immobilized on a carrier, or through a column filled with a bacterial cell or enzyme immobilized on a carrier. In other words, immobilization means that a substance that provides biological activity, in this case, an allulose epimerization enzyme or a glucose epimerization enzyme, or a bacterial cell containing the same, is immobilized on a carrier.

[0056] As used herein, operational stability means that the bioreactor can be operated while maintaining a suitable level of productivity relative to the initial activity in order to continuously produce a target product such as allulose, and is expressed in terms of a normal operation period. When allulose is produced using the compression ratio according to the present invention, for example, the allulose content of the reactant obtained from a fructose-containing substrate having a concentration of 40-50 brix is ​​20% by weight or more, and can be provided for a period of 15 days or more. In addition, the reactant obtained from the substrate supplied at a temperature of 50° C. is supplied to the column packed with the dry beads at a flow rate having a range of 90-100 of the maximum conversion rate, and the flow rate is kept constant until the allulose content decreases to 20% by weight or less, ensuring operational stability.

[0057] In the method for producing allulose, the concentration of fructose used as a substrate for efficient allulose production may be 40 to 75% (w / v), for example 50 to 75% (w / v), based on the total reactants. If the fructose concentration is lower than the above range, it is less economical, and if it is higher than the above range, fructose is not well dissolved, so the fructose concentration is preferably within the above range. The fructose can be used in the form of a solution dissolved in a buffer solution or water (e.g., distilled water).

[0058] In the method for producing allulose, the reaction can be carried out under conditions of pH 6 to 9.5, for example, pH 7 to 9, pH 7 to 8, or pH 8 to 9. The reaction can be carried out under temperature conditions of 30° C. or higher, for example, 40° C. or higher. If the temperature is 80° C. or higher, browning of the substrate fructose may occur, so the reaction can be carried out under conditions of 40 to 80° C., for example, 50 to 75° C., 60 to 75° C., or 68 to 75° C.

[0059] In addition, the longer the reaction time, the higher the allulose conversion rate. For example, the reaction time can be appropriately adjusted in consideration of industrial and economic aspects, and can be selected under conditions that maximize the conversion efficiency of fructose to allulose.

[0060] The psicose obtained from fructose by the method of the present invention can be purified by a conventional method, and such crystallization belongs to the ordinary skill of those skilled in the art, for example, by one or more methods selected from the group consisting of centrifugation, filtration, crystallization, ion exchange chromatography, and combinations thereof. Effect of the Invention

[0061] The dried beads, restored beads, and allulose production using the same according to one embodiment of the present invention have the advantages of being easier to store and distribute due to reduced volume and weight compared to beads before drying, increasing the column loading amount per unit volume to increase allulose production, and having high storage stability, eliminating the problems of weakening of the binding strength and decomposition of beads due to microbial contamination during conventional storage, resulting in the leakage of bacterial cells outside the beads and a decrease in conversion activity, and thus providing stable high allulose production over a long period of time. [Brief description of the drawings]

[0062] [Figure 1] According to one embodiment of the present invention, the immobilized beads were dried, and photographs of the beads obtained before and after drying are shown. [Diagram 2] 1 is a graph showing the amount of water evaporated from pre-dried beads obtained in Examples 1-3 and from dried beads obtained in Example 2. [Diagram 3] 1 shows a photograph of a dried bead before reconstitution and a reconstituted bead obtained after reconstitution according to an example of the present invention. [Figure 4] According to an example of the present invention, a photograph of dried beads on which Microbacterium oxydans and Microbacterium phyllosphaerae cells are immobilized, a stereomicroscope photograph (magnification ×40) and the diameter of the beads are shown. [Diagram 5] Photographs of dried beads on which cells of a recombinant strain of Corynebacterium glutamicum expressing the allulose epimerization enzyme of Clostridium scindens are immobilized, stereomicroscope photographs (magnification ×40), and the diameter of the beads are shown. [Figure 6]1 is a graph showing the productivity increase rate and relative conversion rate of beads obtained by performing an allulose conversion reaction using bacterial cell-immobilized beads according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS EXAMPLES

[0063] The present invention will be described in more detail with reference to the following examples, but the scope of the present invention is not intended to be limited to the following examples.

[0064] Example 1: Production of bacteria-immobilized beads 1-1: Preparation of bacterial cells For the high-concentration cultivation of M. foliorum described in Korean Patent 10-1944103, each seed medium was prepared according to the composition in Table 1, and then sterilized at high temperature and high pressure steam at 121°C for 15 minutes or more to prepare various bacterial culture media. The composition of each seed medium and main culture medium (initial culture medium) was selected as shown in Table 2 below, taking into consideration price competitiveness and productivity, and DPEase was induced with allulose to increase DPEase activity.

[0065] [Table 1]

[0066] To prepare the seed culture, M. foliorum mother strain stored at -70℃ was inoculated into 3ml seed culture medium and cultured at 30℃ for 24 hours as a primary seed culture, and then inoculated into 100ml seed culture medium and cultured at 30℃ for 24 hours as a secondary seed culture. The secondary seed culture medium was finally inoculated into 2L of main culture production medium in a 5L fermenter and cultured at 30℃. Air supplied to the fermenter was sterilized using a 0.2um air filter, and culture was performed according to the fermenter culture conditions in Table 2. In Table 2 below, the air supply unit was vvm (volume of air per volume of liquid per minute, L / min). The feeding method per pH-stat was defined as the increase in carbon source concentration (g / L) in the culture medium (fermentation tank) when the carbon source was added once, and the time of carbon source addition was adjusted so that the f value was 0.25. The composition of the supplemental medium, i.e., the feeding solution, was allulose 400g / L, yeast extract 40g / L, and MnCl2 1mM. According to the basic principle of pH-stat, when the pH exceeded 6.95, sugar was added to reduce the pH, and the pH was adjusted using 9% ammonia water and sugar solution in the pH range of 6.8-6.95. As a result, the bacterial cell concentration and enzyme activity increased as shown in the table above.

[0067] [Table 2]

[0068] 1-2: Production of bacteria-immobilized beads The cultured bacteria are prepared as beads in which the bacteria are immobilized in alginic acid so that they can be used for a long time. Specifically, the culture was carried out as follows. The cultured bacteria were collected by centrifugation, mixed with distilled water to adjust the bacterial concentration to 4% (w / w), and then mixed 1:1 with 4% (w / w) alginic acid dissolved in water to prepare a mixture with a final bacterial concentration of 2% (w / w) and alginic acid of 2% (w / w). The mixture was transferred to a silicon tube connected to a pump that was slowly operated, and the mixture was dropped drop by drop through a syringe (inner diameter 0.20~0.30mm) attached to the end of the tube to mix with 100mM calcium chloride solution and form hardened spherical or elliptical beads (diameter 1.8~2.2mm) while being stirred. The beads produced can be used in the next process, but in order to further increase the internal alginic acid binding power, they can be stored in a refrigerator for 4 to 6 hours while stirring, and then replaced with fresh 100 mM calcium chloride solution, which is then further hardened at a low temperature of 5 to 15°C for about 6 hours to produce immobilized beads in which the final bacteria are captured.

[0069] 1-3: Coating treatment of bacteria-immobilized beads The surface moisture of the alginate beads containing the prepared bacteria was removed by passing them through a mesh sieve, and then water of twice the volume of the beads was added and stirred for 10 minutes. This process was repeated three times to remove the remaining calcium chloride solution. The bacteria-immobilized beads from which calcium chloride had been removed were added to a 0.5% (w / v) chito-oligosaccharide aqueous solution having a volume twice the volume of the beads, and stirred at room temperature for 30 minutes to coat the alginate beads with chito-oligosaccharide. The beads with the completed chito-oligosaccharide coating were passed through a sieve with mesh to remove surface moisture, and then washed with water twice the volume of the beads and passed through a sieve to remove remaining chito-oligosaccharide.

[0070] Example 2: Drying of bacteria-immobilized beads As a specific example, the beads prepared, coated and washed in Example 1 were placed flat on a plate to ensure good drying in a dry oven, and then dried at 45°C (±5°C) for several hours in a hot air circulating manner until the moisture content of the beads was reduced to about 14% or less. Figure 1 shows photographs of the beads before and after drying after drying the bacteria-immobilized beads. The volume, weight, bead diameter, moisture content, and bulk density of the dried beads were measured together with the beads before drying. The specific measurement methods and results are as follows. The beads measurement results are shown in Table 3, and the relative values ​​shown in Table 3 refer to the relative measured values ​​of the volume, weight, diameter, moisture content, and bulk density after drying, with the value of the beads before drying being 100 as the standard.

[0071] (1) Measurement of bead volume change (reactor filling rate) In order to measure the volume reduction of the beads before and after drying in a specific manner, the dehydrated beads of Example 1-3 were measured in a measuring cylinder with a volume of 100 mL as shown in the photograph in FIG. 1. When the volume was measured after drying with hot air, the volume was 10 mL in the measuring cylinder, which indicates a volume reduction of about 10% based on the volume of 100 before drying.

[0072] (2) Measurement of the weight change of beads The weight change before and after drying was 100 g of beads recovered from the solution before drying, and the weight after hot air drying was 7.5 g, which was a decrease of about 7.5% compared to before drying.

[0073] (3) Measurement of apparent density of beads To measure the bulk density of the beads, when the container was filled with 100 mL of undried beads from which moisture had been removed, the result was a weight of 62.2 g and a bulk density of 0.62 kg / L. When the container was filled with 100 mL of dried beads in the same manner, the result was a weight of 69.9 g and a bulk density of 0.7 kg / L.

[0074] (4) Measurement of bead diameter distribution The diameters of the beads obtained before and after the hot air drying were measured by measuring the lengths of 20 beads individually using a Mitutoyo M530-123. The average diameter of the beads before drying was 2.08 mm, but the average diameter of the beads after drying was 1.05 mm. If the average diameter of the beads before drying was taken as 100%, the average diameter of the beads after drying was 50.5% of that before drying, showing a reduction rate of 49.5%.

[0075] (5) Measurement of moisture content of beads The moisture content was measured by measuring the weight change for 30 minutes using a measuring device (A&D MX-50 Moisture Analyzer) with 10g of beads before drying and 10g of beads after drying under infrared irradiation conditions at 125℃. The moisture content of the beads before drying was 95.9% (w / w), while the moisture content of the beads after drying was 9.93% (w / w), resulting in a moisture content of approximately 10% based on the moisture content of the beads before drying being 100.

[0076] [Table 3]

[0077] Example 3: Reconstitution of dried beads 3-1: Restoration of beads The dried beads obtained in Example 2 need to be restored to their original form before they are used in the reaction to convert fructose to allulose. The method of restoration is to place the dried beads in 50 brix (%) crystalline fructose or water, which is a reaction substrate containing fructose, to restore them to their original form. Specifically, the dried beads before restoration were put into a reaction tower, and then the substrate for the conversion reaction used in allulose production (50 brix (%) crystalline fructose adjusted to a temperature of 50°C and pH 6.5-7.2) was passed through or circulated at a feed rate of 0.2-0.5 SV at a reaction temperature of 50°C to hydrate the dried beads and restore them to their original form. Photographs of the dried beads before restoration and the restored beads obtained after restoration are shown in Figure 2.

[0078] 3-2: Analysis of the characteristics of restored beads As shown in the photographs of beads before and after restoration in Figure 3, the shape of the beads after restoration was restored from the dry bead shape before restoration to a spherical or elliptical shape similar to the beads before drying. Therefore, after the restored beads are filled in the reactor, the reaction with the substrate can be smoothly carried out, and the beads have a shape suitable for reaction without channeling problems, where the reaction substrate flows in a specific direction because the beads are uniformly filled in the reactor. As shown in Table 4, the length of 20 beads produced above was measured individually using a measuring device (Mitutoyo M530-123). The average diameter of the beads before restoration was 1.05 mm, while the average diameter of the beads after restoration was measured to be 1.43 mm. If the average diameter of the beads before drying is taken as 100%, the average diameter of the restored beads was about 68.8% of that of the beads before drying, showing a reduction rate of 31.2%. When beads that had undergone the drying and hydration restoration process and pre-dried beads that had not undergone the drying process were each filled into a reactor with the same 100 mL volume of beads at the beginning, the reactor was filled with 52 mL of restored beads after drying (volume %), confirming that the reactor was filled with 52% restored beads.

[0079] [Table 4]

[0080] 3-3: Soaking the restored beads The dried beads that had been restored in Example 3-2 were mixed with a fructose-containing substrate (pH 6.5-7.5) in an amount twice the volume of the beads so that they could be used in a conversion reaction, and then stirred for 10 minutes. This process was repeated twice to replace the inside of the beads with 50Brix(%) crystalline fructose solution. After removing the fructose solution from the surface of the beads, a fructose-containing substrate for manganese ion treatment (50 brix crystalline fructose containing 10 mM MnCl2·4H2O) was added in a volume of at least twice the volume of the beads to fully react with the beads, and the beads were treated with manganese ions by gradually stirring for 30 to 60 minutes in a thermostatic water bath at 50°C. After that, the fructose-containing substrate from the surface of the beads was removed through a sieve, and a fructose-containing substrate for production used in allulose conversion (50 brix crystalline fructose containing 1 mM MnCl2·4H2O) was added in a volume of at least twice the volume of the beads to fully wash the beads, and the substrate was stirred for 10 minutes and replaced with a new substrate, and washing was repeated at least twice to produce beads to be used in the final conversion reaction.

[0081] Example 4: Preparation of dry beads (2) 4-1: Heat treatment of bacteria The Microbacterium strain cultured in Example 1-1 was heat-treated after the culture was completed to increase the activity of the bacteria. Specifically, after the culture was completed in the fermenter, the temperature of the fermenter was gradually increased from 30°C to 60°C while stirring the culture solution with a bacterial cell concentration of 18.5 (OD600nm) at 150 rpm, and the temperature was maintained at 60°C for 1 hour to heat-treat the bacteria. Then, the culture solution was cooled from 60°C to 30°C to obtain a heat-treated bacterial cell culture solution.

[0082] 4-2: Analysis of heat-treated bacterial cells To measure the conversion activity (U / g_cell) before and after the heat treatment of the bacteria, a reaction liquid volume of 1 mL was prepared containing 1 mM MnCl2·4H2O dissolved in 50 mM PIPES buffer solution (pH 7.0), 35 Brix crystalline fructose solution, and a final dry cell concentration of 5 mg / mL. The reaction substrate solution containing the bacteria was then reacted at 70°C for 1 hour, and the supernatant was collected through centrifugation and analyzed by High-Performance Liquid Chromatography (HPLC). The liquid chromatography analysis was performed using a HPLC (Agilent, USA) with an Aminex HPX-87C column (BIO-RAD) equipped with a RID (Refractive Index Detector, Agilent 1260 RID). Water was used as the mobile phase solvent, and the temperature was 80° C., and the flow rate was 0.6 ml / min, and the bacterial activity was analyzed at the conversion concentration of allulose converted from fructose. In addition, the dry bacterial weight of 5 mg / mL used in the bacterial activity measurement was diluted and combined so that the absorbance of the culture solution was 12.5 at OD600nm, and 1 mL was collected, and the supernatant was removed through centrifugation. The dry bacterial concentration was 5 mg when the remaining bacterial cells were multiplied by a dry bacterial conversion factor of 0.4. 1 mL of the reaction substrate used in the conversion reaction was added at a dry bacterial concentration of 5 mg after the supernatant was removed, and the final dry bacterial concentration was adjusted to 5 mg / mL and used for the reaction. The results of comparing the change in cell concentration and activity before and after the heat treatment of the cells are shown in Table 5.

[0083] [Table 5]

[0084] As shown in Table 5, the bacterial cell concentration after heat treatment was slightly lower than that before heat treatment, and the bacterial cell concentration was reduced by about 88% compared to before heat treatment. This is thought to be due to the lysis of the bacterial cells caused by the high temperature during heat treatment at 60℃, resulting in a decrease in the bacterial cell concentration. In addition, when the allulose conversion activity of the bacterial cells before heat treatment was considered to be 100%, the conversion activity was measured after heat treatment of the same amount of bacterial cells as before heat treatment, and it increased by 115% compared to before heat treatment. This is thought to be because when the bacterial cells are heat treated at 60℃, the high temperature causes the lysis of the bacterial cell walls, creating porous cell walls that allow for smooth substrate movement inside the cytoplasm, thereby increasing the allulose conversion activity of the bacterial cells. From the above results, it was confirmed that the decrease in bacterial cell concentration and the increase in bacterial conversion activity through the heat treatment of the bacteria resulted in an increase in the amount of bacteria input of about 12% and an increase in bacterial activity of about 15% during the production of bacteria-immobilized alginate beads, resulting in an increase in productivity of about 25% during bead production compared to before heat treatment.

[0085] 4-3: Production of bacteria-immobilized beads After the cultivation is completed, the bacteria are immobilized in alginic acid to form beads that can be used for a long period of time. Specifically, the heat-treated culture medium was centrifuged to recover the cells, and then mixed with distilled water to adjust the cell concentration to 4% (w / w). The 4% (w / w) alginic acid dissolved in water was mixed with the recovered cells in a weight ratio of 1:1 to produce a mixture with a final cell concentration of 2% (w / w) and alginic acid of 2% (w / w). When heat-treated cells are used, the mixture tends to have a lower viscosity than the mixture using non-heat-treated cells as in Example 1-2. The viscosity of the alginic acid mixture using the heat-treated cells obtained in this example and the alginic acid mixture using the non-heat-treated cells obtained in Example 1-2 was measured at 25°C using a Brookfield viscometer. As a result of the viscosity measurement, the viscosity of the alginic acid mixture in Example 1-2 was 5,580 cps, and the viscosity of the alginic acid mixture obtained in this example was 4,900 cps, which was 87.8% of the level before heat treatment, which is a decrease of about 12%. This is believed to be because the polysaccharides contained in the cells are partially removed by heat treatment, resulting in a lower viscosity. The viscosity (cps) of the alginic acid mixture using the heat-treated and non-heat-treated cells is shown in Table 6 below.

[0086] [Table 6]

[0087] The volume, weight, bead diameter, moisture content, and bulk density of the dried beads were measured together with the beads before drying. The specific measurement method was the same as that in Example 2, and the results are shown in Table 7. The relative values ​​in Table 7 refer to the relative measurement values ​​of the volume, weight, diameter, moisture content, and bulk density after drying, with the measurement value of the beads before drying being 100 as the base value.

[0088] [Table 7]

[0089] 4-4: Restoration of dried beads The beads immobilizing the heat-treated bacteria obtained in Example 4-2 were rehydrated in the same manner as the rehydration method of the dried beads in Example 3-1 and the soaking method in Example 3-3. The rehydrated dried beads were soaked in a fructose-containing substrate (pH 6.5-7.5) so that they could be used in the conversion reaction. As shown in Table 8, when the lengths of 20 beads produced were measured individually with a measuring device (Mitutoyo M530-123), the average diameter of the beads before restoration was 1.02 mm, and the diameter of the beads after restoration was 1.41 mm. When the average diameter of the beads was calculated relative to the average diameter of the beads before drying, which was 100%, the average diameter of the beads after drying was 52.7% and the average diameter of the restored beads was 70.1%. When beads that had undergone the drying and hydration restoration process and pre-dried beads that had not undergone the drying process were each loaded into the reactor at the initial volume of 100 mL, the volume of the restored beads after drying was filled to 48 mL, and the bead volume restoration rate was confirmed to be 48%.

[0090] [Table 8]

[0091] Example 5: Preparation of dry beads (3) 5-1: Production of immobilized bacteria beads and dried beads In order to obtain Microbacterium oxydans and Microbacterium phyllosphaerae bacteria as other species belonging to the same genus other than Microbacterium foliorum, the bacteria were cultured in the same manner as in Example 1-1, and the bacteria were collected by centrifugation after the culture was completed. The Microbacterium oxydans and Microbacterium phyllosphaerae bacteria are the same as the strains described in Korean Patent No. 10-1944104. After the cultivation was completed, the cells were collected by centrifugation, and the collected cells were used to prepare beads having cells immobilized thereon in the same manner as in Example 1-2 for preparing the cells-immobilized beads and in Example 1-3 for coating the cells-immobilized beads. The beads were then dried in the same manner as in Example 2.

[0092] 5-2: Restoration of dried bacteria-immobilized beads 10g of immobilized beads containing dried Microbacterium oxydans or Microbacterium phyllosphaerae bacteria were placed in a beaker, and 200mL of water was added at room temperature, and the beads were stirred at 100 rpm for 30 minutes to carry out the restoration process. The restoration process to the bead shape before drying by hydration with distilled water is shown in Figure 4. 20 beads were individually selected from the beads before drying, the beads after drying, and the restored dried beads produced for each strain, and the bead lengths were measured using a measuring device (Mitutoyo M530-123). The results are shown in Table 9. The beads produced for each strain showed similar diameters before and after drying, and it can be seen that the restoration method can restore them to the same diameter level. In addition, as shown in the photograph of the restored beads in Figure 4, it was possible to restore the beads to a nearly spherical shape identical to that of Microbacterium foliorum cells.

[0093] [Table 9]

[0094] Example 6: Preparation of dry beads (4) 6-1: Preparation of bacterial cells The gene encoding allulose epimerase derived from Clostridium scindens ATCC 35704 (DPE gene; Gene bank: EDS06411.1) was synthesized as a polynucleotide in a modified form optimized for E. coli (named CDPE), and the polynucleotide was inserted into the same restriction enzyme site of the expression vector pCES208 (J. Microbiol. Biotechnol., 18:639-647, 2008) using the restriction enzymes NotI and XbaI (NEB) to prepare a recombinant vector pCES208 / allulose epimerase (pCES_sodCDPE). The recombinant vector (pCES_sodCDPE) plasmid prepared above was transformed into Corynebacterium glutamicum using electroporation to prepare a Corynebacterium glutamicum recombinant strain expressing CDPE enzyme. The recombinant Corynebacterium glutamicum strain expressing the CDPE enzyme can be produced by the method described in Japanese Patent No. 10-1607633.

[0095] 6-2: Production of bacteria-immobilized beads After culturing the strains including the recombinant strain producing allulose epimerization enzyme obtained in Example 6-1, the cells were collected from the culture medium by centrifugation. The collected cells were used to produce beads in the form of cells immobilized thereon in the same manner as in Example 1-2 for producing cells immobilized beads and in Example 1-3 for coating cells immobilized beads, and the beads were dried in the same manner as in Example 2.

[0096] 6-3: Restoration of dried beads 10 g of the dried beads prepared in Example 6-2 were placed in a beaker, and 200 mL of water was added at room temperature, and the mixture was stirred at 100 rpm for 30 minutes to carry out a restoring process, and then allowed to stand for 6 hours. Photographs of the dried beads and the restored beads obtained after 6 hours of hydration, stereomicroscope photographs (magnification x40), and the diameter range of the beads are shown in Figure 5. The average diameter of the restored beads restored by hydration of the dried beads was 1.05 mm. As shown in the photograph in Figure 5, the Corynebacterium glutamicum cell-immobilized beads did not return to their original bead shape even after 6 hours of hydration, and no further changes were observed even after the passage of time.

[0097] As shown in Table 10, the length of 20 beads produced above was measured individually with a measuring device (Mitutoyo M530-123). The average diameter of the dried beads before restoration was 0.93 mm, while the diameter of the beads after restoration was measured as 1.05 mm. When the average diameter of the beads before drying was taken as 100%, the average diameter of the restored beads was about 54% of that of the beads before drying, showing a reduction rate of 46%. When beads that had undergone a restoration process by drying and hydration and undried beads that had not undergone a drying process were initially filled into a reactor with the same 100 mL volume of beads, the volume of the restored beads after drying was filled with 16 mL, and the bead volume restoration rate was confirmed to be 16%. As a result, it was confirmed that the restoration rate of the Corynebacterium glutamicum immobilized dried beads was low, as the shape of the beads did not return to the shape before drying during the restoration process in the photograph of Figure 5.

[0098] [Table 10]

[0099] Example 7: Conversion reaction using immobilized biocatalyst 7-1: Evaluation of conversion activity of beads A productivity comparison experiment was carried out in a reaction tower to compare the allulose conversion activity of the dried beads immobilized with the bacteria in Example 2 and the dried beads immobilized with the heat-treated bacteria in Example 3. Beads (Beads 1) prepared as coated beads in Example 1 that were not subjected to the heat treatment and drying process of the bacteria, beads (Beads 2) prepared as in Example 2 that were not subjected to the heat treatment of the bacteria but were subjected to the drying process, beads (Beads 3) prepared as in Example 4-2 that were immobilized with the heat-treated bacteria but were not subjected to the drying process, and dried beads (Beads 4) prepared as in Example 4-3 that were immobilized with the heat-treated bacteria were prepared. The beads 1 were packed in the reaction tower as they were, and the beads 2, 3 and 4 were packed in the reaction tower after undergoing a restoration treatment in a manner substantially similar to that of Example 3. A fructose-containing substrate of 50 brix (wt%) adjusted to a temperature of 50°C and a pH of 6.5 to 7.2 was passed through the reaction tower packed with the beads to conduct an allulose conversion activity and productivity experiment under a flow rate that maintained an allulose conversion rate of 25% or more, and the experimental results are shown in Table 6 below. The productivity evaluation was performed by comparing the productivity increase rate due to an increase in flow rate with respect to the flow rate of beads 1 at a substrate flow rate at which an initial reaction substrate fructose was converted to an allulose conversion rate of 25% or more with the same bead packing volume of the reaction tower packed with the same volume. In other words, the reaction was carried out using beads 1 to 4 under conditions of the same bead packing volume (mL) of the reaction tower and maintaining an allulose conversion rate of 25% or more, and the productivity was evaluated at the substrate flow rate (mL / min). As shown in Table 12, the productivity of beads that were not subjected to a drying process (beads 1) was set to 100%, and beads 2 to 4 were filled into a reaction tower at the same volume as beads 1 and a fructose-containing substrate was passed through under reaction conditions.These results are for beads 2 to 4. As shown in Table 11, although the bead packing volume (mL) of the reaction tower is the same for beads 1 to 4, it was confirmed that the flow rate at which the allulose conversion rate is maintained at 25% or more increases in the order of beads 1, beads 3, beads 2 and beads 4 due to the increase in allulose conversion activity caused by drying and / or heat treatment of the bacteria. In other words, under the same condition of the bead packing volume (mL) of the reaction tower, a faster flow rate at which the allulose conversion rate is maintained at 25% or more means that the allulose conversion rate of the beads packed in the reaction tower is relatively high. Therefore, it was confirmed that beads 1, which was not subjected to heat treatment and drying process of the bacteria, showed the lowest allulose conversion activity, beads 2, which was not subjected to heat treatment of the bacteria but was subjected to a drying process, had a higher conversion activity than beads 1, and dried beads 4, which had heat-treated bacteria immobilized thereon, had the highest conversion activity.

[0100] [Table 11]

[0101] According to the results in Table 11, when the relative productivity values ​​are set based on the productivity of Beads 1, which did not undergo the drying process and the cell heat treatment process, which is set at 100, the productivity of Beads 3 and Beads 4 showed a significant increase of 146% and 270%, respectively. The reason for this increase in productivity is that the polysaccharides contained in the cells are removed by heat treatment, which increases the reactivity of the allulose convertase contained in the cells with the fructose-containing substrate outside the cells, and the viscosity is reduced by heat treatment, which makes it easier for the fructose-containing substrate to move in the manufactured alginate beads, resulting in increased productivity. In addition, Beads 4, which was produced by drying alginate beads produced using heat-treated bacteria, showed a packing rate that increased by about 200% compared to undried beads (Beads 3) at the same packing volume. Finally, when packed in the same volume as Beads 1, Beads 4 showed a 270% increase in productivity under the same reaction conditions.

[0102] 7-2: Bead reaction stability analysis As described in Example 7-1, the dried beads (beads 4) with the heat-treated bacteria fixed thereon produced in Example 4-3 and the coated beads (beads 1) produced in Example 1, which were not subjected to the bacteria heat treatment and drying process, were treated in the same manner as in Example 7-1 and packed into a reaction tower. The value when a 50Brix (%) crystalline fructose solution adjusted to a temperature of 50°C and a pH of 6.5 to 7.2 was passed through a reaction tower packed with the beads, and an initial flow rate was set to maintain a fructose to allulose conversion rate of 25% or more was set as 100%, and the reduction rate value of the initial allulose conversion rate of the reaction solution by the reaction days is shown in Figure 6. According to the results of the reduction rate against the initial allulose conversion rate in FIG. 6 as in this embodiment, after about 35 days from the initial conversion rate of 100% for beads 1, the reduction rate against the initial conversion rate reached about 55%. In contrast, the stability of beads 4 that were heat-treated and dried was maintained at a reduction rate against the initial conversion rate of about 70% or more after about 35 days from the initial conversion rate of 100%, confirming that the stability of beads that were heat-treated and then dried is higher than that of beads 1. This is believed to be because, when the beads were restored after the bead drying process, the compression rate of the beads was higher than that of Bead 1, and the binding strength of the beads was reduced due to the reaction temperature of 50°C and the Na+ ions added to adjust the pH of the substrate, resulting in a relatively higher binding strength compared to Bead 1 produced by the conventional method, resulting in more favorable results in terms of bead stability.

[0103] Example 8: Storage stability of dry beads The dried beads using the heat-treated cells prepared in Example 4 were stored at storage temperatures of 25°C, 30°C, 37°C, 45°C, and 60°C, and the reduction rate of the allulose conversion activity of the beads depending on the number of weeks of storage was evaluated. Specifically, some beads were taken depending on the number of weeks the beads were stored. 5 mL of reaction substrate (50 Brix crystalline fructose solution adjusted to pH 6.5-7.2) was kept at 60°C in a round flask, and 0.5 g of dry beads were added and reacted for 2 hours to obtain the allulose conversion rate. The reduction rate of allulose conversion activity of the stored dry beads was measured according to the number of weeks of storage by measuring the allulose conversion rate in the same manner as in Example 7-1. The rate of decrease in allulose conversion activity of the beads depending on the storage period and storage temperature of the beads is shown in Table 13.

[0104] [Table 12]

[0105] As shown in Table 12, the reduction rate of the conversion rate immediately after the preparation of the dried beads by the number of weeks of storage shows that the higher the storage temperature, the lower the relative activity. However, at temperatures below 37°C, the allulose conversion activity was maintained at 80% or more for 38 weeks. In particular, even at a high temperature of 60°C, the enzyme stability was maintained at 75% or more after 38 weeks.

Claims

1. The present invention comprises alginic acid or an alginate as a carrier, and a microorganism of the genus Microbacterium that produces an allulose epimerization enzyme immobilized on the carrier, The moisture content is 14% or less, The bacterial cells are heat-treated at a temperature of 40 to 65° C. for 0.1 to 2 hours, and the allulose conversion activity is improved to 101 to 160%. Dried beads for allulose production, having a reaction tower filling rate (volume%) of 35% or less, based on a reaction tower filling rate (volume) of 100% of undried beads having a moisture content of 90% or more.

2. 2. The dry beads according to claim 1, wherein the average particle size of the reconstituted beads obtained after reconstitution with a fructose-containing substrate is 120-190% of the average particle size of the dry beads, based on 100%.

3. 2. The dry beads according to claim 1, wherein the average particle size of the reconstituted beads obtained after reconstitution with a fructose-containing substrate is 1.1 to 1.9 mm.

4. The dry beads according to claim 1, wherein the dry beads have an allulose conversion activity of 60% or more of the beads after storage for 38 weeks at 25°C after production, based on 100% conversion activity of the dry beads immediately after production.

5. The dry beads according to claim 1, wherein the dry beads have an allulose conversion activity of 50% or more of the beads after storage for 38 weeks at a temperature of 60°C after production, based on 100% conversion activity of the dry beads immediately after production.

6. The dry beads according to claim 1, wherein the dry beads have an average apparent bulk density of 0.6 to 0.8 kg / L.

7. 2. The dry beads according to claim 1, wherein the beads are bacteria-immobilized beads produced by adding dropwise a mixture of the bacteria and the carrier to a reaction solution containing a divalent cation chloride compound.

8. The dry beads according to claim 7 , wherein the beads containing the bacteria and the alginic acid carrier include a coating layer of a swelling inhibitor.

9. The dry beads according to claim 8, wherein the swelling inhibitor is at least one selected from the group consisting of chitosan, chitin, polyethylene glycol (PEG), polyethyleneimine (PEI), chito-oligosaccharide, and polylysine.

10. The dried beads according to claim 1, wherein the reconstituted beads obtained after the reconstitution treatment of the dried beads with a fructose-containing substrate have a substrate flow rate (mL / min) at which a 50% by weight fructose solution is passed through and an allulose conversion rate is maintained at 25% or more, based on 100% undried beads, of 110 to 300.

11. The dried beads according to claim 1, wherein the allulose production amount of the beads obtained by restoring the dried beads and carrying out an allulose conversion reaction with a fructose-containing raw material is 110% or more relative to the allulose production amount of beads that have not been subjected to heat treatment and drying of the cells (100%).

12. a step of heat-treating the cells of a strain of the genus Microbacterium producing allulose epimerization enzyme at 40 to 65°C for 0.1 to 2 hours; A step of dropping a mixed solution containing the bacteria and alginic acid or a salt thereof as a carrier into a reaction solution containing a divalent cation chloride compound to form bacteria-immobilized beads; and A method for producing dry beads for allulose production, comprising the step of subjecting the beads to a drying treatment, The heat-treated strain has a relative allulose conversion activity of 101 to 160% compared to the strain before heat treatment; The dry beads have a reaction tower filling rate (volume%) of 35% or less based on a reaction tower filling rate (volume) of 100% of undried beads having a moisture content of 90% or more. A method for producing dry beads for producing allulose.

13. A composition for allulose production comprising the dry beads for allulose production according to any one of claims 1 to 11.

14. A reconstituted bead comprising the dry bead for producing allulose according to any one of claims 1 to 11 and water or fructose liquid, The average particle size of the restored beads is 120 to 190% based on the average particle size (mm) of the dry beads, which is 100%.

15. The restored beads according to claim 14, having a reaction tower filling rate (volume %) of 35% or more based on a reaction tower filling rate (volume %) of 100% of the undried beads.

16. A method for producing restored beads, comprising a step of introducing the dry beads for producing allulose according to any one of claims 1 to 11 into a reaction substrate or water containing fructose.

Citation Information

Patent Citations

  • Immobilized enzyme

    JP1983028285A

  • Method for producing psicose from a fructose-containing substrate

    JP2018533958A

  • Microbacterium strain and method for producing psicose using the same

    JP2018536417A

  • Microbial cell immobilization device and microbial cell immobilization method using the same

    JP2019500037A

  • Psicose-producing bead and preparation method for the same

    KR101616050B1